2015
DOI: 10.1016/j.actatropica.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transmission intensity and age on subclass antibody responses to Plasmodium falciparum pre-erythrocytic and blood-stage antigens

Abstract: Cytophilic immunoglobulin (IgG) subclass responses (IgG1 and IgG3) to Plasmodium falciparum antigens have been associated with protection from malaria, yet the relative importance of transmission intensity and age in generation of subclass responses to pre-erythrocytic and blood-stage antigens have not been clearly defined. We analyzed IgG subclass responses to the pre-erythrocytic antigens CSP, LSA-1, and TRAP and the blood-stage antigens AMA-1, EBA-175, and MSP-1 in asymptomatic residents age 2 years or olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…Significant age-related increases in IgG3 antibodies to CSP have also been reported in areas of stable malaria transmission, but none were identified in unstable malaria transmission where IgG3 responses to CSP declined with age. 73 Here, the IgG1 and IgG4 isotypes were preferentially induced by the LSA-1 antigen. In a study performed in Kenya, John and others reported different data: most antibodies against LSA-1 belonged to the IgG1 and IgG3 subclasses, although IgG2 was observed at lower frequencies.…”
Section: Discussionmentioning
confidence: 78%
“…Significant age-related increases in IgG3 antibodies to CSP have also been reported in areas of stable malaria transmission, but none were identified in unstable malaria transmission where IgG3 responses to CSP declined with age. 73 Here, the IgG1 and IgG4 isotypes were preferentially induced by the LSA-1 antigen. In a study performed in Kenya, John and others reported different data: most antibodies against LSA-1 belonged to the IgG1 and IgG3 subclasses, although IgG2 was observed at lower frequencies.…”
Section: Discussionmentioning
confidence: 78%
“…However, the development of immunity to malaria depends on the balance between cytophilic (IgG1 and IgG3) and non-cytophilic IgG antibodies (IgG4), which interfere with the binding of Fcγ receptors with cytophilic antibodies, complicating the immune response [ 5 , 19 , 20 ]. Noticeably, in the presence of the H131 variant in the FcgRIIA receptor, IgG2 has a cytophilic role, whereas the R131 variant does not bind IgG2 [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…SMC is an administration of full therapeutic doses of these drugs to children aged 3-59 months as monthly interval during period of greatest malaria risk in endemic areas [6]. In these areas, children develop slowly and naturally anti-Plasmodium antibodies and become semi-immune [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria immunity is partial, short-lived, and requires exposure to infected mosquitoes bites to be maintained [7]. Monthly given SMC reduce malaria morbidity in young children in West Africa [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%